Digital Transformation in Human Resource Management: Literature Review on Effectiveness and Implementation Challenges - Didik Sofian Haryadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Human resource managements digital makeover-now a staple of post COVID work life pushes big shifts across firms. Research piles up showing that adding tech to payroll, hiring, or talent reviews boosts speed, lets staff set flexible hours, and sharpens a companys edge. Yet those gains hinge on three building blocks: solid IT pipes, workers who feel at home online, and a culture that values learning-by-linking screens rather than guarding silos. Public bodies and firms in emerging economies run into familiar hurdles-resistance to new ways, knowledge gaps, and tight budgets paid with taxpayer pounds. At the same time, the digital leap invites richer learning loops, a bolder brand image, and faster bursts of innovation as smart-working platforms take center stage. Based on this cross-case look, success calls for one big plan that stitches tech road maps, ongoing staff training, and revised rules into a single fabric. Leaders wishing to boost results through resilient, people-centered digitization will find these pointers practical and timely.